Molecular Features Behind Formation of α or β Co-Crystalline and Nanoporous-Crystalline Phases of PPO - Golla, Manohar; Cozzolino, Antonietta; Nagendra, Baku; Vignola, Emanuele; Daniel, Christophe; Rizzo, Paola; Guerra, Gaetano; Auriemma, Finizia; D’Alterio, Massimo Christian (Frontiers in Chemistry, 2022)
Guest molecular features determining the formation of α and β phases of poly(2-6-dimethyl-1,4-phenylene) oxide (PPO) are explored by collecting literature data and adding many new film preparations, both by solution casting and by guest sorption in amorphous films. Independently of the considered preparation method, α form is favored by hydrophobic and bulky guest molecules while hydrophilic and small guest molecules favor β form. Furthermore, molecular modeling studies indicate that β form inducer guests favor more extended PPO conformations by establishing stronger dispersive interactions with the polymer chain. Thus, the achievement of CC (and derived NC) α and β forms would result from the balance between the energy gain due to host-guest interactions and the internal energy penalty of PPO chains to assume extended conformations.